Factors influencing trainee doctor emigration in a high income country: a mixed methods study - Nicholas Clarke; Sophie Crowe; Niamh Humphries; Ronan Conroy; Simon O'Hare; Paul Kavanagh; Ruairi Brugha (BMC, 2017)
Abstract Background The Global Code of Practice on the International Recruitment of Health Personnel focuses particularly on migration of doctors from low- and middle-income countries. Less is understood about migration from high-income countries. Recession has impacted several European countries in recent years, and in some cases emigration has reached unprecedented levels. This study measures and explores the predictors of trainee doctor emigration from Ireland. Methods Using a partially mixed sequential dominant (quantitative) study design, a nationally representative sample of 893 trainee doctors was invited to complete an online survey. Of the 523 who responded (58.6% response rate), 423 were still in Ireland and responded to questions on factors influencing intention to practice medicine abroad and are the subjects of this study. Explanatory factors for intention to practice medicine in Ireland in the foreseeable future, the primary outcome, included demographic variables and experiences of working within the Irish health system. Associations were examined using univariable and multivariable logistic regression to estimate odds ratios for factors influencing the primary outcome. Qualitative interviews were conducted with 50 trainee doctors and analysed thematically, exploring issues associated with intention to practice medicine abroad. Results There were high levels of dissatisfaction among trainee doctors around working conditions, training and career progression opportunities in Ireland. However, most factors did not discriminate between intention to leave or stay. Factors that did predict intention to leave included dissatisfaction with one's work-life balance (odds ratio (OR) 2.51; 95% confidence interval (CI) 1.53-4.10; P < 0.001); feeling that the quality of training in Ireland was poor (OR 1.82; 95% CI 1.09-3.05; P = 0.002) and leaving for family or personal reasons (OR 1.85; 95% CI 1.08-3.17; P = 0.027). Qualitative findings illustrated the stress of doing postgraduate training with inadequate supervision, lack of ring-fenced training time and pressures on personal and family life. Conclusions Large-scale dissatisfaction with working, training and career opportunities point to systemic factors that need to be addressed by health workforce planners if Ireland is to retain and benefit from a motivated medical workforce, given trainees' perceptions that there are better opportunities abroad.